Quality attributes of biscuit from Acha (digitaria exilis) flour supplemented with cowpea(vigna unguiculata) flour (2011)
Biscuits were produced from blends of acha and cowpea flours. The blends were 100%, 90%, 80%, 70% and 60% acha with cowpea flour to make 100% in each. Proximate composition, trypsin inhibition activity, functional properties including water absorption index, fat absorption index, gelation capacity, bulk density and emulsifying capacity of the blends were determined. Biscuits were produced from the blends. Trypsin inhibition activity, physical properties of the biscuit including break strength, spread ratio, comparative colour analysis and sensory properties of the biscuits were investigated. The results indicated that both protein and trypsin inhibition activity of the blends increased with increase in the amount of cowpea flour substitution. However, significant (p<0.05) reduction in trypsin inhibition activity was noted in the biscuits. Samples with 10% and 20% cowpea substitutions compared favourably with all wheat biscuit in all sensory attributes.